2013
DOI: 10.1080/14733145.2013.860996
|View full text |Cite
|
Sign up to set email alerts
|

Should psychotherapists disclose their own psychological problems?

Abstract: Background: Self-disclosures by psychotherapists can encompass a wide array of content, including information about the personal life of the psychotherapist. Aim: The goal of this study was to empirically assess reactions to psychotherapists disclosing their own personal problems to clients with similar problems. Methodology: This study explored participants' (n = 155) reactions to vignettes describing psychotherapists as either disclosing or not disclosing their own history of psychological problems to client… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 26 publications
(32 reference statements)
0
21
0
1
Order By: Relevance
“…Two thirds of our anonymous sample have not disclosed their lived experience to any of their patients. Appropriate, responsible self-disclosure has been shown to be a powerful and positive tool in psychotherapy (Henretty & Levitt, 2010; Somers, Pomerantz, Meeks, & Pawlow, 2014) and has a long tradition in the addictions field (Dilts, Clark, & Harmon, 1997; Doyle, 1997; Mallow, 1998). Prosumers who have disclosed serve as evidence to colleagues and patients that meaningful mental health recovery is quite possible. Accommodation.…”
Section: Discussionmentioning
confidence: 99%
“…Two thirds of our anonymous sample have not disclosed their lived experience to any of their patients. Appropriate, responsible self-disclosure has been shown to be a powerful and positive tool in psychotherapy (Henretty & Levitt, 2010; Somers, Pomerantz, Meeks, & Pawlow, 2014) and has a long tradition in the addictions field (Dilts, Clark, & Harmon, 1997; Doyle, 1997; Mallow, 1998). Prosumers who have disclosed serve as evidence to colleagues and patients that meaningful mental health recovery is quite possible. Accommodation.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were randomly assigned to one of the eight vignettes. Each vignette was followed by a questionnaire adapted from that used originally in Fox et al (1984); and later used in Somers et al (2014) and McCormic et al (2019). Using a Likert-type scale, participants were asked to rate the therapist 1 ( strongly disagree ) to 5 ( strongly agree ) on the following characteristics, each of which was analyzed as a separate dependent variable (and is listed in full in Table 1): likeable, sincere, warm, able to get along with most clients, capable of understanding clients, considerate of client’s needs, would see a similar therapist, has a strong working relationship, and psychotherapy will be successful.…”
Section: Methodsmentioning
confidence: 99%
“…After reading the vignette to which they were randomly assigned, each participant completed the same nine‐item questionnaire of therapist perception utilized in the Somers et al () study (which itself borrowed from Fox et al, ). Participants rate the therapist 1 = strongly disagree to 5 = strongly agree in these nine categories: likeable, sincere, warm, able to get along with most clients, capable of understanding clients, considerate of client's needs, would see a similar therapist, has a strong working relationship, and psychotherapy will be successful.…”
Section: Methodsmentioning
confidence: 99%
“…For decades, researchers have explored the general topic of therapist self‐disclosure, with little convergence besides the conclusion that judicious self‐disclosure often enhances therapy (especially from the client perspective) and the reminder that benefits to the client, rather than to the therapist, should be the overarching justification of any decision to self‐disclose (e.g., Bloomgarden & Mennuti, ; Cozby, ; Farber, ; Gelso & Palma, ; Godfried, Burckell, & Eubanks‐Carter, ; Henretty & Levitt, ; Henretty, Currier, Berman, & Levitt, ; Hill & Knox, ; Hill, Knox, & Pinto‐Coelho, ; Hill, Mahalik, & Thompson, ; Knox & Hill, ; McCarthy & Betz, ). Within this general topic, a much smaller body of literature focuses on therapists self‐disclosing their own psychological problems to clients (e.g., Fox, Strum, & Walters, ; Kaufman, ; Murphy & Strong, ; Somers, Pomerantz, Meeks, & Pawlow, ). To do so in the clinical setting is certainly not unheard of: Borys and Pope () found that about 40% of therapists have “disclosed details of personal stresses to a client” (p. 286) and 74% believe it is ethically appropriate to make such a disclosure at least “under rare conditions” (p. 288).…”
mentioning
confidence: 99%
See 1 more Smart Citation